Safety and efficacy of formoterol/tiotropium bromide and formoterol/glycopyrronium combination in patients with chronic obstructive pulmonary disease - Ahmad, Siraj; Ahmad, Jameel; Ahmad, Farida; Ahmad, Zuber (International Journal of Research in Medical Sciences, 2023)
Background: Chronic obstructive pulmonary disease is characterized by a progressive development of airflow limitation that is not fully reversible. The study investigated the efficacy and safety of formoterol/tiotropium bromide and formoterol/glycopyrronium combination in patients with chronic obstructive pulmonary disease. Glycopyrrolate, a long-acting anti-muscarinic agent is recently approved for the maintenance therapy of chronic obstructive pulmonary disease in combination with formoterol. However, the studies on glycopyrrolate along with long-acting beta 2 agonist, particularly in Indian patients are limited. Hence it was considered worthwhile to determine safety and efficacy of fixed dose combinations of formoterol/ tiotropium vs. formoterol/glycopyrrolate in grade-2 patients of chronic obstructive pulmonary disease patients. Methods: Efficacy and safety of formoterol/glycopyrrolate and formoterol/tiotropium were compared in Grade-2 patients. Total 68 patients were analysed and the efficacy of treatment was determined by Spirometry, Chronic Obstructive Pulmonary Disease Assessment Test score and Symptom score at day zero (before therapeutic intervention) and at two weeks of interval till 12 weeks. Results: The treatment with inhaled combination of formoterol/glycopyrrolate and formoterol/tiotropium has shown an improvement in spirometric variable Forced Expiratory Volume (in one second) decrease in mean Symptom score and COPD Assessment Test score among the grade-2 Chronic Obstructive Pulmonary Disease patients. Conclusions: Combination therapy of formoterol/glycopyrrolate is non-inferior to formoterol/tiotropium in terms of efficacy and safety profile of patients with chronic obstructive pulmonary disease.